PROBLEMATIKA PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH MUHAMMADIYAH BOTOPUTIH TEMANGGUNG - Hamidulloh Ibda; Muhammad Khoiril Azmi; Faizah Faizah; Nur Alfi Muanayah (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2023)
Arabic language learning for grade 5 students of Madrasah Ibtidaiyah Muhammadiyah Botoputih, Temanggung Regency. These problems will be analyzed and then try to find solutions to overcome them. This type of qualitative research uses a phenomenological approach to reveal the issues or concerns in Arabic language learning in Grade 5 of Madrasah Ibtidaiyah Muhammadiyah Botoputih. Data collection techniques used in-depth interviews, observation, and documentation. The results showed that Arabic language learning at Madrasah Ibtidaiyah Muhammadiyah Botoputih was generally carried out according to the lesson plan. Problems faced by students in learning Arabic consist of linguistic and non-linguistic factors. Linguistic factors consist of sentence structure, sound system, and writing problems, while non-linguistic factors are educational factors, students, methods, facilities, or media. In the linguistic aspect, the solutions are additional material teachers in the form of Nahwu, Saraf, and other material through tajweed learning at Quran Education Center (TPQ), and partnerships with TPQ around the madrasah. In comparison, the solution to non-linguistic problems is the recruitment of teachers with a background in Arabic Language Education and encouraging further master's studies, including teachers in seminars, training, and workshops, habituation to Arabic, providing student motivation and providing teaching materials and digital media to support Arabic language learning. Future research is needed to examine more deeply the innovation of Arabic language learning in Madrasah Ibtidaiyah